Unveiling mode effects in grade 1 vocabulary assessment: the intriguing influence of test mode - Seifert, Susanne; Paleczek, Lisa; Schöfl, Martin; Weber, Christoph (Frontiers in Education, 2024)
Background: Vocabulary knowledge plays a pivotal role in academic development, particularly among Grade 1 students. To support students in their academic development, effective assessment instruments in educational settings are crucial. The XXX is introduced as a tool designed to evaluate receptive vocabulary in German-speaking countries in print and in digital mode.Objectives: This study aims to investigate mode effects in the XXX among Grade 1 students, comparing vocabulary gains in digital and print versions. Additionally, it explores the influence of student characteristics, such as gender and language status, and examines item-level differences between the two modes in order to gain a more comprehensive understanding of test performance.Design: The research design entails a longitudinal approach, following children (n = 421) from the beginning to the end of Grade 1, varying the test modes (digital or print) only at second measurement (40% receiving the print version), while at first measurement all children worked with the digital version.Results: Baseline comparisons of test mode groups indicated almost no significant differences. In terms of growth in vocabulary during Grade 1, an ANOVA with repeated measures revealed a main effect for time, indicating increased performance in both groups at second measurement. Moreover, an interaction effect between time and test mode group showed that the print group exhibited higher gains in the vocabulary test compared to the digital group. Further analysis using MNLFA confirmed that the print mode group outperformed the digital group overall and that four items were also individually affected by differences between the digital and print versions.The study emphasizes the need for nuanced investigations into the impact of test mode on student performance and suggests incorporating observational methods to comprehensively understand student interactions with digital and print modes. In acknowledging potential variations in performance, educators and policymakers need to tailor practices to accommodate the demands of hybrid test procedures and to consider the role of digital competence in shaping testing experiences.